DETECTION OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) BY AUTOMATED AND MANUAL METHODS - N.KAUR; R.PRASAD; A.VARMA (International Journal of Pharma and Bio Sciences, 2013)
Methicillin resistant Staphylococcus aureus has become an enormous problem for health care providers because it is hard to treat and is sometimes called super bug. Early and accurate detection of methicillin resistance in Staphylococcus aureus is essential for the treatment of overt infections and the implementation of infection control practices. The phenotypic detection of mecA-mediated resistance has presented ongoing challenges due to low level of methicillin resistance and heterogeneous nature of methicillin resistance in S.aureus. This study compares the performance of three different methods, Vitek 2 compact system (bioMerieux, France), Cefoxitin disc diffusion method and chromogenic media for the detection of methicillin resistant Staphylococcus aureus recovered from patients in tertiary-care hospitals. A total of 107 clinical isolates of Staphylococcus aureus were tested for methicillin resistance by Vitek 2 compact, automated ID/AST system. As a result, 23 isolates of Staphylococcus aureus were detected as methicillin resistant. The cefoxitin disk diffusion tests detected 100% (23 isolates) of all the MRSA and Chrom ID MRSA also showed similar good results (100%) of sensitivity and specificity for the detection of MRSA after 24 h of incubation.